2006
DOI: 10.1007/s11084-006-9018-5
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Surface Directed Membrane Assembly

Abstract: The transition from non-living to living matter may have resulted from the self-organizing properties of organic molecules and their interactions with a chemically rich inorganic environment. We have shown that a solution containing RNA, fatty acids and clay produces structures that contain a potentially catalytic surface (clay) and a potential informational biopolymer (RNA) encapsulated within a membrane. This highlights the ability of mineral surfaces to bring together and organize key components of primordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
111
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(116 citation statements)
references
References 19 publications
2
111
0
3
Order By: Relevance
“…The hypothesis is experimentally supported by studying vesicle formation in the presence of various minerals, e.g., pyrite and montmorillonite. 159,160 However, experiments aimed at synthesis of amino acids and nucleic bases from CO 2 using FeS/H 2 S system failed, 161 and it was shown that sulphide minerals stimulate degradation of RNA by catalysing the hydrolysis of phosphodiester bonds. 146 …”
Section: Reactions On Sulphide Surfacesmentioning
confidence: 99%
“…The hypothesis is experimentally supported by studying vesicle formation in the presence of various minerals, e.g., pyrite and montmorillonite. 159,160 However, experiments aimed at synthesis of amino acids and nucleic bases from CO 2 using FeS/H 2 S system failed, 161 and it was shown that sulphide minerals stimulate degradation of RNA by catalysing the hydrolysis of phosphodiester bonds. 146 …”
Section: Reactions On Sulphide Surfacesmentioning
confidence: 99%
“…Other studies on membrane self-assembly processes which allow cellular compartmentalisation have been carried out with amphiphiles ( [75] and references therein). Hanczyc and colleagues [76] found that the presence of naturally occurring clay minerals, such as montmorillonite, can help in the assemblage of vesicles and, in the process, bring bound RNA …”
Section: A Vesicular Origin Of Lifementioning
confidence: 99%
“…Many mineral surfaces promote vesiculation (Hanczyc et al 2003;Hanczyc et al 2007), in this case the mineral surfaces seems to facilitate bilayer formation by promoting ordering of molecules on their surfaces in specific configurations.…”
Section: Self-assembly Processes and Protocell Stabilitymentioning
confidence: 99%